Tantangan Guru Pendidikan Agama Islam di Era Modern dalam Penggunaan Artificial Intelligence (AI): Challenges for Islamic Religious Education Teachers in the Modern Era in the Use of Artificial Intelligence (AI) - Ahmad Choirun Najib; Darnoto (STAI Ma'had Aly Al-Hikam Malang, 2024)
In the modern era, the use of Artificial Intelligence (AI) technology has become an integral part of Islamic Religious Education (Pendidikan Agama Islam; PAI) learning. However, PAI teachers face many challenges in using AI. The article was prepared using a qualitative approach and library research type of research. The article’s findings are divided into three. First, PAI teachers are required to carry out their roles as Mudarris, Mu'allim, Mu'addib and Murabbi. Second, AI has an important role in PAI learning, such as making it easier for teachers and students to access information. Third, there are six types of challenges for PAI teachers in using AI, namely digital literacy problems, lack of facilities and infrastructure, lack of preparation, problems related to ethics, theological problems and educational interaction problems. Therefore, PAI teachers are required to overcome these various challenges, so that the use of AI really has a positive impact on PAI learning. Di era modern, penggunaan teknologi Artificial Intelligence (AI) telah menjadi bagian integral dalam pembelajaran Pendidikan Agama Islam (PAI). Namun, guru PAI menghadapi banyak tantangan dalam penggunaan AI. Artikel disusun menggunakan pendekatan kualitatif dan jenis penelitian studi pustaka. Temuan artikel dibagi menjadi tiga. Pertama, guru PAI dituntut menjalankan perannya sebagai Mudarris, Mu’allim, Mu’addib dan Murabbi. Kedua, AI memiliki peran penting dalam pembelajaran PAI, seperti mempermudah guru dan siswa untuk mengakses informasi. Ketiga, ada enam jenis tantangan guru PAI dalam penggunaan AI, yaitu problem literasi digital, minimnya sarana-prasarana, kurangnya persiapan, problem terkait etika, problem teologis dan problem interaksi edukatif. Oleh sebab itu, guru PAI dituntut untuk menanggulangi berbagai tantangan tersebut, agar penggunaan AI benar-benar memberikan dampak positif bagi pembelajaran PAI. Kata Kunci: Guru PAI; Pendidikan Agama Islam; Era Modern; Artificial Intelligence (AI).